Trans-Atlantic Slave Trade - Database

The Making of Modern Law
A collection of digital archives covering classic and contemporary legal traditions in America, Britian, Europe, Latin America, Asia, and other jurisdictions.
Keywords: _no subscription

Freedom on the Move | Cornell University

AARDOC: African-American Religion: A Documentary History Project Home Page
Keywords: _open access

Daniel A. P. Murray Pamphlet Collection (Library of Congress)
"African American Perspectives" gives a panoramic and eclectic review of African American history and culture and is primarily comprised of two collections in the Rare Book and Special Collections Division: the African American Pamphlet Collection and the Daniel A.P. Murray Collection with a date range of 1822 through 1909. Most were written by African-American authors, though some were written by others on topics of particular importance in African-American history. Among the authors represented are Frederick Douglass, Ida B. Wells-Barnett, Benjamin W. Arnett, Alexander Crummel, Emanuel Love, Lydia Maria Child, Kelly Miller, Charles Sumner, Mary Church Terrell, and Booker T. Washington, among others.
Keywords: _open access

African American Women Writers of the 19th Century - Divisions, Schomburg Center Research (NYPL)
African American Women Writers of the 19th Century guide includes a digital collection of published works by 19th-century black women writers, biographies for each author, citations and much more
Keywords: _100+; _open access

Houston Mutiny and Riot Records (South Texas College of Law Houston Digital Collections)
Keywords: _open access

Independent Voices
About this Collection: Independent Voices is an open access digital collection of alternative press newspapers, magazines and journals, drawn from the special collections of participating libraries. These periodicals were produced by feminists, dissident GIs, campus radicals, Native Americans, anti-war activists, Black Power advocates, Hispanics, LGBT activists, the extreme right-wing press and alternative literary magazines during the latter half of the 20th century. Independent Voices is ma...
Keywords: _open access

Black Freedom Struggle - ProQuest
Open to everyone at blackfreedom.proquest.com
Keywords: _open access

Documenting the American South
Texts, images, and audio files related to southern history, literature, and culture. Subjects covered include church history, African American history, North Carolina state history, oral and social histories, and more.
Keywords: _open access

Black Thought and Culture - Alexander Street Press
Collection d’écrits (autres que fictionnels) provenant de personnalités américaines noires majeures issues du monde politique, religieux, journalistique et autre.
Keywords: _NO SOFIA; _open access

Black Studies Center - ProQuest
Scholarly essays, recent journal articles, historical newspaper articles, reference books, and other sources for the study of the African Diaspora.
Keywords: _no subscription

Slavery, Abolition and Social Justice - Adam Matthew Publications
Sources et archives portant sur l'esclavage et les mouvements antiesclavagistes dans le Monde atlantique
Keywords: _UdeM only

African American Newspapers (1827-1919) - Accessible Archives
Keywords: _UdeM only